Acute Korsakoff Syndrome Following Mammillothalamic Tract Infarction - Yoneoka, Yuichiro; Takeda, Norio; Inoue, Akira; Ibuchi, Yasuo; Kumagai, Takashi; Sugai, Tsutomu; Takeda, Ken-ichiro; Ueda, Kaoru (American Journal of Neuroradiology, 2004)
Summary: There are limited case reports of structural lesions causing Korsakoff syndrome. This report describes acute Korsakoff syndrome following localized, bilateral infarction of the mammillothalamic tracts (MTTs). Axial T2-weighted imaging revealed the lesions at the lateral wall level of the third ventricle and diffusion-weighted imaging confirmed that the left lesion was new and the right old. Korsakoff syndrome persisted 6 months after the onset. This case suggests that bilateral MTT dysfunction can lead to Korsakoff syndrome.